Cost-Effectiveness of currently available diagnostic tools for diagnosis of pediatric tuberculosis under national tuberculosis elimination program - Ragini Bhatia; Anil Chauhan; Kulbir Kaur; Monika Rana; Meenu Singh (Wolters Kluwer Medknow Publications, 2023)
In India, children do not get diagnosed with tuberculosis (TB) for reasons such as lack of screening modality at the health-care settings, inadequate sputum sample, and low detection rate. This study aims to assess various modalities for diagnosis of pediatric TB and their cost-effectiveness. Cost-effectiveness was found for various diagnostic modalities for TB diagnosis in children of India below 15 years of age. TrueNat MTB was the intervention being compared to GeneXpert MTB and sputum microscopy. Evidence pertinent to effectiveness and cost per test, and health benefits in terms of disability adjusted life years were researched and documented. Modeling a cohort of children through a decision tree and assimilating costs and disability-adjusted life years (DALYs) at each step gave results in the form of cost-effectiveness. Interventions were compared by calculating the cost-effectiveness ratio. The results revealed that TrueNat is more cost effective (Rs. 9450/DALY averted) compared to GeneXpert MTB/RIF (Rs. 9750/DALY averted). The incremental cost effectiveness ratio of TrueNat with respect to GeneXpert was found to be Rs. 5925 per DALY averted. Diagnosis through TrueNat point of care (POC) will avert 962 more DALYs compared to GeneXpert. As is evident from the results, TrueNat does alleviate disability caused by TB in children as more DALYs are averted. At an additional cost of Rs. 5925 to avert one DALY, which is below the gross domestic product (GDP) per capita for India (for 2021, it was $2277), TrueNat can have significant health benefits.